Pengaruh Job Crafting terhadap Work Engagement pada Sales Marketing - Nindy Puspita Rachman; Anna Rozana (Bandung Conference Series: Psychology Science, 2023)
Abstract. Business success can occur with employees who are tied to their work so that employees are able to do their work optimally. One of the factors is work engagement. Work engagement is considered a three-dimensional construction and is defined as a state of mind related to positive and satisfying work characterized by, vigor, dedication, and absorption (Schaufeli & Bakker, 2010). The job demands and job resources model can be a predictor of work engagement. Efforts to balance job The job demands and job resources model can be a predictor of work engagement. Efforts to balance job demands and job resources can use job crafting. Job crafting is the changes that individuals make on their own initiative to balance the demands and resources they earn from their work (Tims et al, 2012). This research aims to influence job crafting on work engagement in sales marketing carvawan. Subiek this research is 27 employees of sales marketing contracts at Bank Danamon. This research uses population techniques. The research method, which is used is quantitative with causality research design using multiple regression. The measuring instruments used are the Job Crafting Scale (ICS) from Tims et al (2012) adapted by Angga Januar et al and Utrecht Work Engagement Scale (UWES) from Schaufeli & Bakker (2002). The results showed that there was a positive influence of job crafting on work engagement of 82.1% (R square - 821) with the most influential job crafting dimension on work engagement was Increasing Structural Job Resources of 30.5%. Abstrak. Keberhasilan bisnis dapat terjadi dengan adanya karyawan yang terikat dengan pekerjaannya sehingga karyawan mampu melakukan pekerjaannya dengan optimal. Salah satu faktornya yaitu work engagement. Work engagement dianggap sebagai konstruksi tiga dimensi dan didefinisikan sebagai keadaan pikiran yang berhubungan dengan pekerjaan yang positif dan memuaskan yang ditandai dengan vigor, dedication, dan absorption (Schaufeli & Bakker, 2010). Model job demands dan job resources dapat menjadi prediktor work engagement. Upaya menyeimbangkan job demands dan job resources dapat menggunakan job crafting. Job crafting yaitu perubahan yang dilakukan individu atas inisiatif mereka sendiri untuk menyeimbangkan tuntutan dan sumber daya yang mereka peroleh dari pekerjaannya (Tims et al, 2012). Penelitian ini bertujuan untuk menguji pengaruh job crafting terhadap work engagement pada karyawan sales marketing. Subjek penelitian ini adalah 27 karyawan kontrak sales marketing di Bank Danamon. Penelitian ini menggunakan teknik populasi. Metode penelitian yang digunakan adalah kuantitatif dengan desain penelitian kausalitas menggunakan multiple regression. Alat ukur yang digunakan adalah Job Crafting Scale (JCS) dari Tims et al (2012) diadaptasi oleh Angga Januar et al dan Utrecht Work Engagement Scale (UWES) dari Schaufeli & Bakker (2002). Hasil penelitian menunjukkan terdapat pengaruh positif job crafting terhadap work engagement sebesar 82,1% (R square = .821) dengan dimensi job crafting yang paling berpengaruh terhadap work engagement adalah Increasing Structural Job Resources sebesar 30,5%.